2019
DOI: 10.1111/cdev.13275
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teacher–Child Race/Ethnicity Matching and Classroom Diversity on Children's Socioemotional and Academic Skills

Abstract: Mounting evidence suggests teacher-child race/ethnicity matching and classroom diversity benefit Black and Latinx children's academic and socioemotional development. However, less is known about whether the effects of teacher-child matching differ across levels of classroom diversity. This study examined effects of matching on teacher-reported child outcomes in a racially/ethnically diverse sample of teachers and children, and classroom diversity moderation using multilevel models. Data were drawn from a profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…[29][30][31][32] In the education world, Black students report higher satisfaction and demonstrate better academic achievement with a Black teacher. [33][34][35] Thus, this study suggests the need to improve the quality of information available on YouTube regarding prostate cancer screening in Black men, including that provided by Black presenters. An interesting finding was that DISCERN scores were significantly higher for videos created after the 2018 USPSTF guidelines calling for informed decision making about PSA screening.…”
Section: Discussionmentioning
confidence: 96%
“…[29][30][31][32] In the education world, Black students report higher satisfaction and demonstrate better academic achievement with a Black teacher. [33][34][35] Thus, this study suggests the need to improve the quality of information available on YouTube regarding prostate cancer screening in Black men, including that provided by Black presenters. An interesting finding was that DISCERN scores were significantly higher for videos created after the 2018 USPSTF guidelines calling for informed decision making about PSA screening.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, research has shown same‐ethnic and cross‐ethnic friends can have differential influence academic and psychosocial outcomes (Benner & Wang, 2017; Kawabata & Crick, 2015), and even ERI (Jugert et al, 2020). Teacher–child race/ethnicity matching, in conjunction with classroom diversity, has been shown to be associated with greater social‐emotional and academic skill for Black and Latinx children (Rasheed et al, 2019). Thus, we encourage scholars to also consider the dynamic of friend and teacher race/ethnicity matching as a potential factor on the effects they are observing across the various levels of the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Teacher–child racial congruence also did not directly predict school readiness. This was somewhat surprising given its import in studies of older children (Cherng & Halpin, 2016; Dee, 2005; Egalite & Kisida, 2018; Rasheed et al, 2020). Perhaps, the influence of teacher–child racial congruence on school readiness becomes more apparent as children move into formal schooling.…”
Section: Discussionmentioning
confidence: 99%
“…All children should have the opportunity to learn in classrooms that are shepherded by teachers who are warm, responsive, and capable of developing relationships with them that are positive, respectful, and fair (Crouch et al, 2014; Drewery, 2016; Gouveia‐Pereira et al, 2003). Sadly, children from racial minority groups have a higher likelihood of being negatively perceived by teachers and tend to experience harsher treatment from them than their White counterparts (Gansen, 2020; Martinez, 2020; Petras et al, 2011; Rasheed et al, 2020; Yates & Marcelo, 2014). Additionally, teachers perceive themselves as having closer relationships with White students than with African American children (Kesner, 2000).…”
Section: Introductionmentioning
confidence: 99%